Baptism studies in the original Christian baptism, its history and conflicts, its relation to a state or national church and its significance for the present time - Warns, Johannes, 1874-1937; Lang, George Henry, 1874-1958 (London, UK Paternoster, 1957)
INcludes bibliographial referernces and index.
Brethren writer and translator.
Keywords: Believer's baptism; Brethren movement -- practices